Electrophysiological responses to lateral shifts are not consistent with opponent-channel processing of interaural level differences - Ozmeral, Erol J. (J Neurophysiol, 2019)
Cortical encoding of auditory space relies on two major peripheral cues, interaural time difference (ITD) and interaural level difference (ILD) of the sounds arriving at a listener’s ears. In much of the precortical auditory pathway, ITD and ILD cues are processed independently, and it is assumed that cue integration is a higher order process. However, there remains debate on how ITDs and ILDs are encoded in the cortex and whether they share a common mechanism. The present study used electroencephalography (EEG) to measure evoked cortical potentials from narrowband noise stimuli with imposed binaural cue changes. Previous studies have similarly tested ITD shifts to demonstrate that neural populations broadly favor one spatial hemifield over the other, which is consistent with an opponent-channel model that computes the relative activity between broadly tuned neural populations. However, it is still a matter of debate whether the same coding scheme applies to ILDs and, if so, whether processing the two binaural cues is distributed across similar regions of the cortex. The results indicate that ITD and ILD cues have similar neural signatures with respect to the monotonic responses to shift magnitude; however, the direction of the shift did not elicit responses equally across cues. Specifically, ITD shifts evoked greater responses for outward than inward shifts, independently of the spatial hemifield of the shift, whereas ILD-shift responses were dependent on the hemifield in which the shift occurred. Active cortical structures showed only minor overlap between responses to cues, suggesting the two are not represented by the same pathway. NEW & NOTEWORTHY Interaural time differences (ITDs) and interaural level differences (ILDs) are critical to locating auditory sources in the horizontal plane. The higher order perceptual feature of auditory space is thought to be encoded together by these binaural differences, yet evidence of their integration in cortex remains elusive. Although present results show some common effects between the two cues, key differences were observed that are not consistent with an ITD-like opponent-channel process for ILD encoding.